Model Sampling: A Stochastic Cost-Volume-Profit Analysis. - Liao, Mawsen (The Accounting Review, 1975)
The article presents an accounting model of cost-volume-profit (C-V-P) analysis. The use of stochastic analysis in a C-V-P analysis model is a great step forward in providing more useful information for profit planning. This model has been depicted as a limit analysis, since the assumptions of the independent model parameters and the normalcy of the resulting profit function are not true in all cases. Instead of using single estimates of model parameters in the C-V-P analysis model, sampling C-V-P analysis treats the model parameters as random variables. The objective of model sampling is to calculate one profit value from each set of the random model parameters. Then, by repeating the sampling process a sufficient number of times, certain characteristics of the profit distribution can be derived. The purpose of model sampling is to determine the sample profit points in the profit distribution rather than to identify the distributional form. However, the C-V-P model sampling is not restricted to the problem with independent and normal distribution model parameters only. An example in this article demonstrates the application of model sampling to a C-V-P analysis problem with dependent and non-normal distribution model parameters.